Sport Education model effects in the social climate classroom, perceived competence and intent to be physically active: an extended study in primary education - Martínez de Ojeda Pérez, D.; Méndez-Giménez, A.; Valverde Pérez, J. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2016)
The main objective was to evaluate the effects of implementing longitudinal model of Sport Education on the classroom social climate, perceived competence and intention to be physically active in elementary students. 51 3rd and 4th primary students (34 boys and 17 girls) with a mean age of 8.86 years (SD = .75) participated in the study, from a public school in the province of Murcia. A quasi-experimental design was performed with measures pretest, posttest-1, posttest-2, posttest-3, at the end of each of the three sports seasons applied. Quantitative and qualitative instruments (specific questionnaires, interviews to teacher and students, and diary of professor), were used to deepen the dependent variables from the teacher-student perspective. The results showed how the intervention produced significant improvements in the perception of the social climate (mainly men) and that these increased levels were maintained over time. The intention to be physically active reached high and constant levels; women in posttest-3 progressed to levels similar to men. Similarly, the perceived competence remained high with a tendency to decline in the last season in men. The correlations between the dependent variables were positive and moderate. Qualitative results deepen these issues. The potential of the model is discussed to maintain high and stable levels in the variables studied, which could impact on reducing disruptive behavior in the classroom and increase levels of physical activity after school.